In Search for the Scope of Main Subject Matter within Article 4(2) of Directive 93/13 after Andriciuc. Practical Consequences of the General CJEU Pronouncements - Sitnik, Piotr (Polish Review of International and European Law, 2020)
The paper delves into the intricacies surrounding the ‘main subject matter’ requirement with a view to delineating its scope by reference to CJEU jurisprudence. Specifically, regard is had to the recent case of Andriciuc, its dictum and potential ramifications it may have for the judicial purview in the field of unfair terms control. Practice in recent years has brought to the fore the issue of indexation clauses as the focal point for doctrinal disputes. Comprehensive analyses of the main subject matter have also been carried out by Polish courts at all instances, including that in the Supreme Court, within the context of claims brought by consumers who entered into loans denominated in the Swiss Franc following the events of the so-called ‘Black Thursday’. The paper strives to decode the practical ramifications of the CJEU’s general doctrinal interpretations, offeringsuccinct corollaries pertaining to the compatibility with the EU standard, of the judicial interpretations of Poland’s courts with regard to the concept.